Resource Utilization and the Use of Bone Stimulators among Operatively and Nonoperatively Managed Scaphoid Nonunion Patients - Rachel C. Hooper, MD; Yuan Zeng, MS; Lu Wang, PhD; Kevin C. Chung, MD, MS (Plastic and Reconstructive Surgery, Global Open, 2023)
Background:. The prevalence of bone stimulator use among nonoperatively and operatively managed scaphoid nonunion patients is unknown. We hypothesize that bone stimulators are a relatively underutilized treatment for scaphoid nonunion patients. Methods:. We used the 2009–2017 Truven Marketscan Research Databases to identify patients with closed scaphoid fractures and performed an analysis of variance test to determine resource utilization and bone stimulator use among these patients. Results:. A total of 36,611 patients with scaphoid fractures were identified: 30,143 were managed nonoperatively and 6468 were managed operatively. Nonunion was diagnosed in 500 (1.66%) nonoperatively and in 1211 (19%) operatively managed patients. Bone stimulators were used in less than 2% of nonoperatively and operatively managed scaphoid nonunion patients. Conclusion:. Lack of trust in the technology and heterogenous (and occasionally burdensome) requirements for insurance approval are barriers to bone stimulator use; however, surgeons should examine how this technology may fit into the treatment algorithm for these difficult cases.